Associations between ambient, personal, and indoor exposure to fine particulate matter constituents in Dutch and Finnish panels of cardiovascular patients - Janssen, N (BMJ Group, 2005)
Aims: To assess the relation between ambient, indoor, and personal levels of PM(2.5) and its elemental composition for elderly subjects with cardiovascular disease. Methods: In the framework of a European Union funded study, panel studies were conducted in Amsterdam, the Netherlands and Helsinki, Finland. Outdoor PM(2.5) concentrations were measured at a fixed site. Each subject's indoor and personal PM(2.5) exposure was measured biweekly for six months, during the 24 hour period preceding intensive health measurements. The absorbance of PM(2.5) filters was measured as a marker for diesel exhaust. The elemental content of more than 50% of the personal and indoor samples and all corresponding outdoor samples was measured using energy dispersive x ray fluorescence. Results: For Amsterdam and Helsinki respectively, a total of 225 and 238 personal, and 220 and 233 indoor measurements, were analysed from 36 and 46 subjects. For most elements, personal and indoor concentrations were lower than and highly correlated with outdoor concentrations. The highest correlations (median r>0.9) were found for sulfur and particle absorbance, which both represent fine mode particles from outdoor origin. Low correlations were observed for elements that represent the coarser part of the PM(2.5) particles (Ca, Cu, Si, Cl). Conclusions: The findings of this study provide support for using fixed site measurements as a measure of exposure to particulate matter in time series studies linking the day to day variation in particulate matter to the day to day variation in health endpoints, especially for components of particulate matter that are generally associated with fine particles and have few indoor sources. The high correlation for absorbance of PM(2.5) documents that this applies to particulate matter from combustion sources, such as diesel vehicles, as well.